Analisis Kejadian Dispepsia terhadap Faktor Pemicunya - Saputri, Syarifa Anita; Indriani, Nurul; Kresnapati, I Nyoman Bagus Aji (Department of Pharmacy, Bumigora University, 2025)
Analysis of Dyspepsia Incidence Against Trigger Factors in Patients at the Narmada Health Center. Dyspepsia is a common condition characterized by discomfort or pain in the upper abdomen, and can affect a person's quality of life and have a negative impact on the sufferer's productivity. The purpose of this study was to analyze the incidence of dyspepsia against its triggering factors in Narmada Health Center. This study used a quantitative method with a cross-sectional research design, with a questionnaire instrument that was valid (0.612 - 0.951) and reliable (> 0.90). Results The prevalence of dyspepsia in this study was 164 people based on data from the Narmada Health Center. The frequency of knowledge levels, consuming frogs, exercising on an empty stomach, smoking habits, and the begibung tradition did not show a significant relationship with the incidence of dyspepsia in the community (p-value> 0.05). Meanwhile, the incidence of dyspepsia has a significant relationship with the frequency of consumption of spicy foods, sour foods, fatty foods, raw foods, consuming coffee with a value (p-value <0.05). The conclusion of this study is that the frequency of consumption of spicy foods, sour foods, fatty foods, raw foods, consuming caffeine and drugs are risk factors for the incidence of dyspepsia in the patients at Narmada Health centers